Lessons Learned Risk Management Issues in Genetic Counseling - Schmerler, Susan (Springer New York : Imprint: Springer, 2008)
Lessons Learned Risk Management Issues in Genetic Counseling Susan Schmerler, Children's Hospital of St. Joseph's Regional Medical Center, Paterson, New Jersey Malpractice suits are filed every day. Even the most experienced practitioners are not immune to potentially career-ending malpractice charges. With so much at stake, how do you avoid lawsuits and protect yourself against legal action? Susan Schmerler, a lawyer and expert witness, as well as a respected genetic counselor for more than 30 years, will help you survive and thrive in today's litigious society. The only book devoted exclusively to this specialty, Lessons Learned details the risk management issues involved in genetic counseling practice, and offers solid strategies for minimizing the risk of costly, career-damaging malpractice suits. Schmerler clearly identifies areas of practitioner liability and demonstrates how they may be averted, so counselors can better manage their practice while lowering the risk of legal action. Examples drawn from relevant court cases illustrate typical issues in malpractice, negligence, and breach of contract suits. With this in-depth knowledge, readers can refine their goals toward increased self-protection as well as client care. Included in the coverage: Sources of liability in genetic counseling practice. Case examples involving wrongful birth/life, confidentiality, billing, supervision issues. Anatomy of a malpractice suit-obligations, duties, standards, defense. Proper documentation. Guidelines for professional response to lawsuits. Plus helpful summaries, charts, tables, graphics, and online research ideas. This is must reading for genetic counselors and trainees. But the lessons of Lessons Learned extend far beyond the field, making the book a significant resource for health care risk managers and administrators, attorneys, marriage and family counselors, and other professionals in psychology and public health.